Sosialisasi Inovasi Pelayanan Publik: Membangun Sistem Informasi untuk Meningkatkan Akses dan Kualitas Layanan di Desa Tijue - Laila Qadriah; Maryanti; Husaini; Achmady, Sayed (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
This service analyzes the sources and channels of information, as well as the flow and access patterns within Tijue village. As part of the community service, training sessions and socialization efforts were carried out to educate the residents about the information system, along with several recommendations aimed at enhancing the system's effectiveness for the village population. The study highlights issues with information access, despite the availability of sources and interpersonal communication channels. A key challenge identified is the residents' limited ability to access information. The author suggests establishing a Village Information Center to offer integrated and coordinated services to meet the community's information needs. This case study is one of the efforts focused on understanding the flow and accessibility of information in Tijue village.